CONFLICT IN THE PROCESS OF VALUE TRANSFORMATION: KONFLIK DALAM PROSES TRANSFORMASI NILAI - Ahmad Misbahul Anam (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2021)
An inevitability of social life is the presence of conflict. Its appearance in the perspective of the harmony of a nation is seen as leaving only problems, but in the framework of societal change can actually be a stimulus of creativity. Every individual involved or the public who watches it, will be helped to choose which is positive and which is negative. That is, conflict can actually be seen as something positive for the birth of science or how to overcome it, even conflict is made to control changes in society.